PELATIHAN PEMBUATAN LILIN AROMATERAPI UNTUK MENGOPTIMALISASI HASIL PERKEBUNAN CENGKEH DI DESA HARGOSARI - Astuti, Laily Puji; Azizah, Luthfiana; Pratiwi, Widiyatami Hanum; Anggraini, Rosa Denik; Ni’am, Asrorun; Maulana, Rahmad Yusuf; Muslim, Imam; Syah, Muhammad Jafar; Kumalasari, Devi; Ningrum, Wakhidiyah Tristya; Rohmadani, Myewa Citra; Faiz, Alif Salma; Khasanah, Binti Nur; Wijaya, Akbar Tito; Fatmaningrum, Diyah; Ismadi, Ismadi; Prasetyo, Darji (LP2M Institut Agama Islam Ngawi, 2024)
Aromatherapy candles are candle that provide a therapeutic effect when burned, such as for alternative medicine, decoration or air freshener. The benefit of aromatherapy candles made from the essential oil of the clove plant is that it is a health treatment that contains high levels of eugenol to help the wound healing process. The aim of this research is to provide educational training to community members about the process of managing essential oils from clove plants into aromatherapy candles. The method used is practice and explanation of materials for making aromatherapy candles with community members, especially housewives and teenagers. The activity of training on making aromatherapy candles was positively supported by the village head and officials as well as local representatives and hamlets. The results of carrying out these activities can produce essential oil products to optimize the yield of clove plants in Hargasari village. This training hopes that community members will be able to manage essential oils from clove plants well and can increase natural resources optimally. Abstrak: lilin aromaterapi adalah lilin yang memberikan efek terapi apabila dibakar seperti untuk alternatif pengobatan, penghias maupun pengharum ruangan. Manfaat lilin aromaterapi dari minyak atsiri cengkeh yaitu sebagai pengobatan kesehatan yang memiliki eugenol tinggi untuk membantu proses penyembukan luka. Adapun tujuan pengabdian ini memberikan edukasi pelatihan pada warga masyarakat tentang bagaimana proses pengelolaan minyak atsiri dari tanaman cengkeh menjadi lilin aromaterapi. Metode yang digunakan yakni praktek dan penjelasan materi pembuatan lilin aromaterapi dengan warga masyarakat khususnya ibu-ibu rumah tangga dan remaja. Kegiaan pelatihan pembuatan lilin aromterapi didukung secara positif oleh kepala desa dan perangkat serta perwakilan warga dukuh setempat. Hasil pelaksanan kegiatan tersebut dapat membuat produk minyak atsiri untuk mengoptimalkan hasil tanaman cengkeh di desa hargosari. Pelatihan ini diharapkan warga masyarakat mampu mengelola minyak atsiri dari tanaman cengkeh dengan baik serta dapat meningkatkan sumber daya alam yang optimal. Kata Kunci: pelatihan, lilin aromaterapi, cengkeh